Measurement of ammonia line intensities in the 1.5 µm region by direct tunable diode laser absorption spectroscopy. (December 2021) - Pogány, Andrea; Werhahn, Olav; Ebert, Volker
Highlights: high-accuracy intensities of 19 near-infrared ammonia absorption lines. three of the lines are highly relevant for environmental monitoring. strictly metrological uncertainty assessment. improved uncertainty and accuracy compared to literature data. Abstract: We have measured ammonia line intensities using direct tunable diode laser absorption spectroscopy (dTDLAS) in the 1.5 µm region, and provide new or improved line intensities for 19 absorption lines between 6547 and 6552 cm -1 . Our experimental setup was carefully designed to minimize bias and error. Our measured line intensities have at least comparable, or considerably lower uncertainties, and reveal significant differences (up to 40%) compared to literature data. Furthermore, we provide an in-depth quantification and discussion of key sources of uncertainty complying with the guide to the expression of uncertainty in measurement (GUM). Independent NH3 trace amount fraction measurements indicate that our line intensities for the three strongest lines (6548.61, 6548.80 and 6548.92 cm -1 ) are more accurate than the data listed in the HITRAN database, while our uncertainties are also considerably lower (1, 1 and 3%).